Opinions Regarding Societal Resilience - Marinescu, Liviu Mihail; Sirbu, Gabriela Elena (Acta Universitatis Danubius. Relationes Internationales, 2023)
It is discussed extensively about resilience as the individual's ability to overcome difficult moments in life, and the possibility of collectives to overcome unfavorable situations. In all resilient situations, successes are possible through the use of willpower, physical and mental, being restored to the ability of the subjects to continue the actions oriented in a positive sense. The resilient approach is feasible only in the case of establishing some constructive objectives, avoiding the narrow self. Resilient intentions and concern cannot be made publicly known, being the case of the existence of a private, confidential approach of the positively oriented individual. In a synergistic manner, the concerns of the resilient subjects must be directed unitarily for the benefit of the collective. The success of the resilient approach is given by the harmonized involvement of weight structures: the mind (thinking), the heart (soul) and the physical body (natural reactions). Societal resilience must be the result of thinking and action at the level of the resilient state, the effort being corroborated with the individual effort undertaken by the common citizen.